Effectiveness of Giving Herbal Oil on Pressure Ulcers Management in Intensive Care Unit (ICU) Patients: Systematic Review - Nonah Suciati; Iwan Purnawan; Ridlwan Kamaluddin (International Journal of Biomedical Nursing Review, 2023)
Background: Intensive Care Unit is a unit to treat critical patients who need intensive care and monitoring. This can pose many risks, one of which is getting pressure ulcers/decubitus ulcers. Pressure ulcers are wounds caused by continuous compression of soft tissue. Prevention of pressure ulcers can be done by treating the patient's skin using herbal oil. Purpose: To identify the effectiveness of giving herbal oil on the treatment of pressure ulcers in ICU patients. Methods: The literature search was carried out using the PICO framework. This systematic review is limited to articles published in 2011-2021. The databases used are Google Scholar, PubMed, Sage Journal, Science Direct, and ProQuest with the keywords (oil OR herbal oil) AND (decubitus OR pressure ulcers OR bedsores) AND (critical patient). The selection of articles follows the PRISMA flow. Assessment of article quality was carried out by supervisors and authors using the risk of bias from The Cochrane's Collaboration. Results: Based on the seven articles reviewed, five recommended oils were obtained, including olive oil, Virgin Coconut Oil (VCO), fish oil, almond oil and henna oil. The oil is applied by three methods, including by smearing without massage, smearing with massage and dressing. The instruments used are the Braden Scale, Suriadi Sanada Scale, Pressure Ulcer Scale for Healing (PUSH), International NPUAP/EPUAP Pressure Ulcer Classification System, micro life NC100 infrared thermometer and Mini Nutritional Assessment (MNA). Conclusion: Herbal oil can be applied by various methods as a complementary therapy to prevent and treat pressure ulcers in patients in the ICU.